Social psychology - Myers, David G. (McGraw-Hill College, 2013)
How many of the students in your Social Psychology course are Psychology majors? Business? Sociology? Education? In this edition, the author once again weaves an inviting and compelling narrative that speaks to ALL of your students regardless of background or intended major.